ARENAL-A Supplementary Tool in Learning Anatomy and Common Acquired Diseases of The Human Urinary System - Mohamad Zainal, Nurul Hayati; Naim, Muhammad Haris; Mohd Nor, Nurul Huda; Thani, Suryati Mohd; O K Rahmat, Rahmita Wirza (International Journal of Human and Health Sciences (IJHHS), 2024)
They can visibly observe the kidney and its anatomical position through a detailed 3D kidney model instead of 3D on paper. For patients, as compared to reading hospital pamphlets, ARENAL enables them to augment the learning process better due to its accessibility and interactivity. Results: The user acceptance testing (UAT) (n= 10) revealed that this was their first interaction with AR (60%), strongly agreed that ARENAL is functioning smoothly (60%) and strongly agreed on its easiness to use (50%). Most respondents have a higher acceptance of ARENAL and suggested complementing more quizzes, games, activities, colours and additional functions to the 3D model for more interactivity. Conclusion: In conclusion, most respondents were satisfied with ARENAL, thus, ARENAL has the potential to be used as a supplemental tool in learning the anatomy and common acquired diseases of human US. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S17